Purpose of Physical Education as Perceived by PE Students: The Goal Orientation Approach - Maro, Cyprian N. (Papers in Education and Development, 2018)
The study examined the perceived purpose of physical education (PE) among (N=400) students in secondary schools in Tanzania (average age 17.1 years). Confirmatory factor analyses and reliability and correlation analyses supported the psychometric properties of the questionnaires. The results revealed that the perceived purpose of PE was conceptually related to how the students define success/failure in PE. Thus, how the purpose of PE was defined depended on whether the students focused on skill mastery, trying hard, and personal improvement (i.e. task orientation) or being better than other students and wanting to show that (i.e., ego orientation) or both. The results showed that task orientation related to the belief that PE develops lifetime skills and pro-social behaviours. On the other hand, ego-oriented students endorsed the view that PE was a means towards enhancing one ' s social status and teaching maladaptive behaviours. Conclusively, the findings validate in a cross-cultural context the arguments regarding the relationship between an individual ' s goals and world-view of the purpose of the activity. High ego-oriented students perceived enhancing their socio-economic status as the purpose of PE, thus providing no positive effects on motivation, and giving little support to the PE teachers to encourage the competitive ethos. To achieve morality and equality and make young people feel that physical activities should teach them to try their best, co-operate, obey the rules and authority, and become good citizens, then task-orientation among PE students should be fostered through systematic training by PE teachers.